Program Lingkungan Perumahan Berbasis Pendidikan dalam Mewujudkan Pembangunan Pendidikan Berkelanjutan - Mufidah, Yenny Imroatul (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
Educational planning can only be fully understood within the context of broader institutional and social planning practices. In the Indonesian context the government in creating intelligent society, by incorporating the aspect of education in the vision of regional development includes increasing the responsibility and care of the family towards the policy of increasing the quality and equity of education in order to create an education-based housing environment. This research is a qualitative descriptive research to describe the evaluation of the results of the implementation of housing-based housing program in Mojokerto City. The subjects of this research are policy makers and stakeholders consisting of Mojokerto Mayor, Secretariat of Education and Culture Office of Mojokerto City, Pokja KMBP, KMBP Post, Motivator Team of Kota and Kelurahan of Miji, and Task Force of Study Compulsory and six residents in Miji urban village. Techniques of collecting data in the form of documentation, interviews, and observation. Data analysis by reduction, presentation and conclusion. The results of the study indicate that housing-based housing programs can provide positive results. Judging from the formal evaluation approach that refers to the program outcome indicators: the indicators of motivation in the family education, motivation given by the parents to the child in the form of support and encouragement. Availability of educational facilities at home, which is given is still not standard because the learning place used is the living room. Compulsory school hours have been running well in the family environment, at compulsory school hours at 18:00 to 19:00 school-age children must be in the home environment. Control of learning, behavior and association is good because parents have been watching the child's learning behavior both in the family environment and school environment by supervising the learning process of children through learning outcomes in school. Family harmony provides good results because parents have a special way to create family harmony by doing activities together to bring interaction between family members. A clean, healthy, neat, safe and comfortable lifestyle was created well by parents and children.